A hybrid therapy for arrhythmogenic congestive cavity in a single ventricle. (18th November 2020) - Izumi, Gaku; Yokoshiki, Hisashi; Tachibana, Tsuyoshi; Takeda, Atsuhito
Abstract: We describe a 15-year-old girl who underwent intraoperative catheter ablation for the ventricular tachycardia associated with Ebstein's anomaly with functional pulmonary atresia and a small right ventricle (RV) after Fontan surgery. The computed tomography showed the dilated right atrium and RV due to the failure of RV plication. The activation mapping revealed that the ventricular tachycardia showed a focal pattern originating from the atrialized RV (aRV). With careful preparations, the procedure of catheter ablation combined with the adjustment of Starnes fenestration and plication of RV/atrialized RV was very effective for this patient.